The effect of underwired and sports bras on breast shape, key anthropometric dimensions, and body armour comfort - Malbon, Christopher; Knock, Clare; Critchley, Richard; Carr, Debra J. (Sage, 2021)
This study follows on previous research which investigated the comfort and types of bras worn by UK female police officers when wearing body armour and performing typical activities. This controlled study involved a cohort of 31 female police officers and investigated three main areas. Firstly the effect of professional bra fitting on size and comfort, secondly the effect of wearing an underwired bra or a sports bra on comfort and ability to perform certain actions, and thirdly the effect of an underwired bra and sports bra on key anthropometric data in relation to the fitting of body armour.
Keywords: female body armour; professional bra fitting; anthropometric chest measurements; sports bra; Underwired bra